The First Magallanes-Elcano Global Circumnavigation Trip: A Look at the Initiatic Encounters with South American Biodiversity [el Primer Viaje de Circunnavegación Global Magallanes-Elcano: Comen- Tarios a Los Iniciáticos Encuentros Con la Biodiversidad Sudamericana] - Castro-Morales, S (Universidad de Magallanes, 2022)
500 years after the Magallanes-Elcano Expedition along the South American coasts, we analyzed the vernacular records of biological species reported in the Relación of this trip, written by Antonio Pigafetta, in addition to the Derrotero, by Francisco Albo. We found 40 vernacular names corresponding to 42 scientifically nominated species (13 plants, 12 birds, 6 fishes, 9 mammals, and 2 mollusks). Most of these records come from Bahía de Santa Lucía (Brazil) and Bahía de San Julián (Argentina), followed by Estrecho de Magallanes (Chile), Santa Cruz River and Santa María Cape (Argentina). Out of 42 species, 26 (62%) are currently in some category of conservation concern, according to the IUCN. © 2022